2014
DOI: 10.1165/rcmb.2013-0043oc
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase 3 Dysregulation in a Murine Model of Neonatal Lung Injury

Abstract: Bronchopulmonary dysplasia (BPD), a common chronic respiratory disease that occurs after premature birth, is believed to be secondary to oxidative damage from hyperoxia and inflammation, which leads to impaired alveolar formation and chronic lung dysfunction. We hypothesized that extracellular superoxide dismutase (SOD)3, an antioxidant uniquely targeted to the extracellular matrix (ECM) and alveolar fluid, might have a different response (downregulation) to hyperoxic injury and recovery in room air (RA), ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Certain studies performed on premature babies concluded that severe lung injury and inflammatory changes may be mitigated and the requirement for mechanical ventilation may be reduced with no associated adverse effects by prophylactic intratracheal administration of recombinant human CuZn superoxide dismutase (rhSOD). Prophylactic administration of intratracheal rhSOD to premature babies at birth with a birth weight ranging from 600 to 1,200 g and a high risk of developing BPD was associated with reduced respiratory episodes, including wheezing, asthma and respiratory infections, as concluded in a randomized placebo-controlled trial (98). Trials have suggested that rhSOD is able to prevent long-term lung injury due to oxygen exposure in high-risk pre-mature neonates (99,100).…”
Section: Recent Preventive Therapymentioning
confidence: 90%
See 1 more Smart Citation
“…Certain studies performed on premature babies concluded that severe lung injury and inflammatory changes may be mitigated and the requirement for mechanical ventilation may be reduced with no associated adverse effects by prophylactic intratracheal administration of recombinant human CuZn superoxide dismutase (rhSOD). Prophylactic administration of intratracheal rhSOD to premature babies at birth with a birth weight ranging from 600 to 1,200 g and a high risk of developing BPD was associated with reduced respiratory episodes, including wheezing, asthma and respiratory infections, as concluded in a randomized placebo-controlled trial (98). Trials have suggested that rhSOD is able to prevent long-term lung injury due to oxygen exposure in high-risk pre-mature neonates (99,100).…”
Section: Recent Preventive Therapymentioning
confidence: 90%
“…An upcoming therapy for the prevention of BPD development is the supplementation of human recombinant anti-oxidant enzymes (92,98). Certain studies performed on premature babies concluded that severe lung injury and inflammatory changes may be mitigated and the requirement for mechanical ventilation may be reduced with no associated adverse effects by prophylactic intratracheal administration of recombinant human CuZn superoxide dismutase (rhSOD).…”
Section: Recent Preventive Therapymentioning
confidence: 99%
“…Neonatal animals have been shown to have a greater increase in antioxidant availability, particularly by AECs, in response to a hyperoxia challenge relative to adult animals . However, over time, when the neonatal protection against oxygen diminishes, antioxidant responses, such as Nrf‐2 activity and the availability of enzymes such as superoxide dismutase, glutathione reductase and catalase, may be impaired …”
Section: Discussionmentioning
confidence: 99%
“…37,38 However, over time, when the neonatal protection against oxygen diminishes, antioxidant responses, such as Nrf-2 activity and the availability of enzymes such as superoxide dismutase, glutathione reductase and catalase, may be impaired. 35,[39][40][41] Limited information is available about the effects of hyperoxia on claudin localization and expression. Recently, Xu et al 21 In AECs isolated from neonatal lungs, we showed a significant down-regulation of claudin-3 and claudin-18 expression with hyperoxia exposure, but no alteration in claudin-5 protein abundance.…”
Section: Discussionmentioning
confidence: 99%
“…MDA affected the stability and the transcriptional functions of Nrf2. Notably, it was suggested that PECGGp activated SOD3 expression via Nrf2 pathway, protecting rat hearts against oxidative damage by decreasing MDA levels [49]. …”
Section: Discussionmentioning
confidence: 99%